Perceptions of Students Toward Physics Learning Strategies at the Secondary Level (Pragyaratna प्रज्ञारत्न, 2023)
The study aimed to find out the perception of students towards physics learning strategies and to analyze perceptions of the student’s learning strategies. The research design is quantitative in nature and follow survey design with random sampling methods to take the perceptions of 500 students for the sample size was selected 75 students from five government school towards physics learning strategies. Data was collected by using paper based closed ended, which utilized a Likert scale format. Descriptive statistics such as frequency, percentage, mean and standard deviation were used for the analysis of data. The study revealed that students generally exhibited a positive attitude towards learning physics and showed a preference for social interaction, group study, ICT based learning, logic resonance, collaborative learning, note taking, and note making, problem solving, laboratory method and feedback from teachers. While the use of lecture method and rote learning strategies, students gave a negative response. The study emphasized the importance of considering students' opinions and preferences when designing and implementing effective learning strategies. It suggested that teachers and educators prioritize the use of collaborative learning, laboratory methods, feedback and problem solving strategies in physics classes. A physics lab is required to effectively understand the material for students towards visualizing concepts in physics were positive from the statements that visualizing concepts helps students remember and understand physics easily and quickly. This study also highlighted the need for further research to explore the integration of these effective learning strategies into physics instruction in order to enhance student learning outcomes.